Bioconversion of rice straw into acetone-butanol-ethanol by Clostridium sporogenes A3 - Mohamad Remli, Nurul Atika (2014)
The inevitable depletion of the world’s energy supply and unstable oil market have renewed the interest of society in searching for alternative fuels. In addition to depletion of petroleum fuels, environmental issues like greenhouse effect, global warming and climate change, are also the issues to be resolved worldwide. Biobutanol has been considered as a suitable alternative to be a source of fuel. Abundant biomass from various agriculture sectors could be a source for biobutanol production. Rice straw is one of the most abundant lignocellulosic biomass that has a great potential as a cheap and affordable substrate for the production of reducing sugars and biofuel such as biobutanol. The feasibility of rice straw as a source of sugar production was evaluated in this study. The effectiveness of alkaline pretreatment on rice straw was assessed taking into consideration the yield of reducing sugars and changes in the morphological and chemical composition of rice straw. Pretreatment of rice straw by 2% (w/v) NaOH and KOH with autoclaving at 121°C, 15 psi (10 min) could be promising pretreatment methods for sugar production. Alkaline pretreatments with 2% (w/v) KOH and NaOH followed by thermal pretreatment at 121°C, 15 psi (20 min) resulted in 58.5 to 64.5% higher conversion rate of reducing sugars production than untreated rice straw showing that alkaline pretreatments were effective even when a higher temperature was used. FTIR and SEM investigations showed that alkaline pretreatments caused chemical and morphological changes in the rice straw. The peaks of the cellulose and lignin materials were decreased after alkaline pretreatment, indicating that some cellulose and lignin were degraded. The reducing sugars obtained were then converted to acetone-butanolethanol (ABE) by Clostridium sporogenes A3. The total acetone-butanol-ethanol (ABE) production by locally isolated C. sporogenes A3 using rice straw hydrolysate was 1.58±0.11 g/L in which 0.73±0.05 g/L was butanol after 120 h of fermentation. Higher ABE yield was obtained from rice straw hydrolysate when compared to using commercial glucose as a carbon source. Increasing concentration of sugars in the rice straw hydrolysate to 40 g/L did not showed any improvements to the total ABE obtained. A higher level of ABE was obtained (1.72±0.39 g/L) at initial culture pH 5.5 (37ºC), in which 0.93±0.22 g/L was butanol. In comparison, higher yield of ABE was obtained when using C. acetobutylicum ATCC824. The ABE yield obtained was 0.33 which corresponds to 64% of ABE increment compared to fermentation using C. sporogenes A3. These results suggested that the reducing sugars obtained from pretreated rice straw could be used as a substrate for ABE fermentation by C. sporogenes A3 and C. acetobutylicum ATCC824. This will reduce carbon emission and our dependency on fossil fuel, and at the same time makes butanol as one of our future energy for many applications.